A bifactor model of the Wong and Law Emotional Intelligence Scale and its association with subjective well-being. Issue 4 (4th July 2021) - Di, Meilin; Jia, Ning; Wang, Qiuling; Yan, Wenjing; Yang, Kairong; Kong, Feng
ABSTRACT: Although the Wong and Law Emotional Intelligence Scale (WLEIS) has been validated in many studies, it has not been validated with bifactor model. Study 1 conducted a confirmatory factor analysis with a sample of 525 Chinese university students aged 18–30 years old, and found that the bifactor model with a general factor and four specific factors showed the best fit to the data. Study 2 cross-validated these findings in another 724 adult sample aged 17–56 years old, and the measurement invariance between students and employees was obtained. Besides, the results of Structural Equation Modeling demonstrated that the general factor could predict the three components of subjective well-being (i.e., life satisfaction, positive affect, and negative affect), but only the specific factor of Use of Emotion could predict positive affect. Moreover, there were no differences in these relations between students and employees. Implications and future directions of the findings were discussed.